The Labor Process and ADR: Conflic Resolution in the Case of Academic Harassment in the University Enviroment - Pérez Martell, Rosa (2024)
The seriousness of the existing academic harassment and the solutions, sometimes successful, sometimes not so successful, given by higher education institutions, justifies this work. The objectives pursued are to investigate a subject where there is a relevant international, European and national regulation of academic institutions of higher education; to analyze the legal precepts on harassment in Spanish universities, also the Law of University Coexistence, as well as the doctrine and jurisprudence applicable to these cases. In this context, the use of the social jurisdiction is promoted due to the outstanding protection it grants to the party most in need of protection and due to the characteristics of the social jurisdictional order. Often, the labor route may be an option that the victim may consider to be the best way to resolve these situations, in those cases that are more favorable to him/her. Finally, it is intended to make a critical review of the current regulations to provide solutions to the unfortunate cases of academic harassment. The methodology used has been focused, firstly, on the collection of materials and appropriate bibliography, to subsequently carry out an initial review and an ordering of the broad thematic compiled, then proceed to the study of the theoretical framework, followed by the analysis of the facts raised, its subsequent assessment, formulate hypotheses that are valid in the analysis of the rules indicated, with the study of the applicable jurisprudence, as well as the doctrine. It concludes by providing new proposals aimed at putting an end to this scourge, going deeper in the search for solutions in this field, including answers from Artificial Intelligence.